2022
DOI: 10.3892/etm.2022.11368
|View full text |Cite
|
Sign up to set email alerts
|

Resibufogenin inhibits the malignant characteristics of multiple myeloma cells by blocking the PI3K/Akt signaling pathway

Abstract: Resibufogenin (RBG) is an active ingredient of toad venom that also has antitumor potential. The present study aimed to investigate the role of RBG in multiple myeloma (MM) and the underlying action mechanism involving the PI3K/Akt signaling pathway. A human MM cell line, RPMI8226, was treated with RBG and/or insulin-like growth factor 1 (IGF-1; an activator of the PI3K/AKT signaling pathway). Cell viability and apoptosis were detected using Cell Counting Kit-8 and flow cytometry, respectively. Cell migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Increasing numbers of studies have reported that EMT‐like transcriptional patterns are activated in MM 16,31–33 . To confirm whether E2F2 regulated EMT in MM, we measured the expression of EMT‐related genes in E2F2‐knockdown and E2F2‐overexpressing MM cell lines (H929 and MM.1S cells respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing numbers of studies have reported that EMT‐like transcriptional patterns are activated in MM 16,31–33 . To confirm whether E2F2 regulated EMT in MM, we measured the expression of EMT‐related genes in E2F2‐knockdown and E2F2‐overexpressing MM cell lines (H929 and MM.1S cells respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing numbers of studies have reported that EMTlike transcriptional patterns are activated in MM. 16,[31][32][33] To confirm whether E2F2 regulated EMT in MM, we measured the expression of EMT-related genes in E2F2knockdown and E2F2-overexpressing MM cell lines (H929 and MM.1S cells respectively). Our results showed that the suppression of E2F2 increased the expression of epithelial markers (TJP1 and E-cadherin [E-Cad]) and decreased the expression of mesenchymal markers (Vimentin and Twist1) (Figure 2A,B).…”
Section: E2f2 Positively Regulates MM Cell Emt Migration and Invasion...mentioning
confidence: 99%